PENERAPAN TUNTUTAN PIDANADI BAWAH MINIMUM KHUSUS DALAMDELIK KORUPSI PEMERASAN DALAM JABATAN - Agus Kurniawan, (2022)
In order to achieve a more effective goal of preventing and eradicating corruption, Law of the Republic of Indonesia Number 31 of 1999 concerning Eradication of Criminal Acts of Corruption as already stated in the Law of the Republic of Indonesia amended by the Law of the Republic of Indonesia Number 20 of 2001 containing different criminal provisions with previous laws, one of which was to determine a specific minimum criminal threat, but in its implementation a special minimum criminal threat that clashes between the principle of legal certainty with the principle of justice and the principle of benefit Law, while the Public Prosecutor in carrying out the prosecution must also be able to realize certainty, the applicable law, justice and truth based on the law and observing religious norms, politeness, and decency, also must have human values, law, and justice that live in society, as observed Law of the Republic of Indonesia Number 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia. This paper explains that the Public Prosecutor can apply criminal charges below the specific minimum in the corruption offense of extortion in office, based on the prosecution's discretion and contemporary theory of sentencing purposes. The type of research used in this paper is a type of normative research which analyzes secondary data. This study explains the theoretical basis or criteria for the application of criminal charges under the special minimum in corruption offenses, extortion in office